A Maturity Approach to the Rate of Heat Evolution in Concrete - Ballim, Y.; Graham, P.C. (My University, 2003)
This paper discusses the use of the concept of maturity as a means of combining the effects of time and temperature in describing the rate of heat evolution from hydrating cement in concrete. The proposed maturity approach allows the rate of heat evolution determined from an adiabatic test to be expressed in a form which is independent of the starting temperature of the test. This relationship can then be directly used in a time-temperature prediction model which requires a solution of the Fourier equation for heat flow.
Early-age cracking as a result of temperature induced stresses can be a serious problem in mass concrete structures or in concrete structural elements in which a high cement content concrete is used. These stresses are induced by temperature differences in the concrete as a result of the heat liberated by hydrating cement. A strategy that is aimed at controlling or limiting such cracking must include a reliable determination of the space-time distribution of temperature throughout the concrete element under consideration.